Ejaan baharu - Abdul Rahman bin Haji Mohammad (Kuala Lumpur, Nadatini, 1972)
New spelling of the Malay language
Cover title: Ejaan baharu; a complete guide with easy references to the new spelling system for bahasa Malaysia
In English; with examples in Malay
Koleksi Sumbangan : Prof. Dr. Mohd. Safar Hasim
Keywords: Malay language -- Orthography and spelling